Effects of different temperatures on sex differentiation and critical thermosensitive period of little yellow croaker (Larimichthys polyactis) - Jing-Ye Feng; Ze-Hui Wang; Fu-Liang Wei; Min Yu; Ting Ye; Chu-Nan Wu; Feng Liu; Dan-Dan Guo; Bao Lou; Qing-Ping Xie (Aquaculture Reports)
This study aimed to determine the thermosensitive period and effect of temperature on sex differentiation in L. polyactis. The results showed that the male-biased sex ratio was 50.9, 57.8, and 97.9 % in the 18, 24, and 31℃ groups at 90 days post-fertilization (dpf), respectively. Additionally, eggs, larvae, or juvenile fish were transferred from untreated water to 18 and 31℃ every 6 – 9 days from 0 to 55 dpf to clarify the thermosensitive period. The results demonstrated that the critical thermosensitive period was 19 – 25 dpf and the male-biased ratio reached 77.8 %. Exposure to 31℃ resulted in 74.1 and 69.6 % male-biased ratios during the 25 – 31 and 31 – 37 dpf periods, respectively, after the critical thermosensitive period. Histological observations indicated that long-term exposure of juvenile fish to 31℃ induced oocytes and/or ovary degeneration, followed by sex reversal to the testis. This study demonstrates that the sex differentiation of L. polyactis is significantly affected by high temperatures during the thermosensitive period and provides basic information on the sex differentiation of L. polyactis. It also provides a theoretical foundation for the sex-controlled breeding of L. polyactis.